The 'double-edged sword' of a sessional academic career. Issue 3 (16th April 2019) - Richardson, Julia; Wardale, Dorothy; Lord, Linley
ABSTRACT: There have been widespread changes to working arrangements and employment relationships, including significant decreases in continuing/full-time employment contracts. This trend is particularly notable in academia, with more universities relying on the expertise of sessional, teaching-focused academics. This qualitative study extends understanding of this important group of professionals, identifying sessional work as a 'double-edged sword' and suggesting a typology of sessional academic careers to be tested in future research. It reports on the diversity among sessional academics, some enjoying the autonomy and flexibility of this working arrangement, others seeking more job security and greater alignment with continuing employment. It also identifies synergies and contradictions between sessional academic careers and key themes in the contemporary careers literature.